Effect of flooring system on maintenance behaviours of cows - UPADHYAY, DEEPAK; SINGH, MUKESH; GAUR, GYANENDRA KUMAR; BHARTI, PANCH KISHOR; VERMA, MED RAM (The Indian Journal of Animal Sciences, 2021)
To evaluate the effect of floor on maintenance behaviours of cow in loose housing system, four groups, viz. T0 (concrete in covered and brick-paved in open area), T1 (concrete in covered and sand bed in open), T2 (rubber mat in covered and sand bed in open) and T3 (rubber mat in covered and brick-paved in open) were studied. Feeding was the major activity (39–44%) of day, with significant difference between groups. In covered area, lying and standing rumination, while in open area idling, were significantly different between groups during day. During night lying-rumination was major activity (62–69%). Night idling, standing-rumination, lying and lying-rumination behaviour, were significantly different between groups. Overall most of the time in each group was devoted to lying-rumination (45–53%) and feeding (18–21%). Area wise, open area was more occupied and posture wise sitting posture dominated in all the groups. Overall feeding, idling and standing-rumination in open, lying-rumination (in open or covered area), sleeping, total standing time and total sitting time were significantly different between groups. Feeding time showed positive trend in rubber matted floor (T2, T3). More lying-rumination and sleeping time was seen in rubber matted covered area. Sand bedding in open area reduced the standing and standingrumination activity, while promoting the sitting/lying time. Rubber matting in covered area and sand bedding in open area, was found favourable for maintenance behaviour of dairy cows.